Economics of patenting - V. G. Zinov; O. I. Kupriyanova (Ekonomika Nauki)
The article presents an economic analysis of expenses for patenting and by using leading technical universities as an example, it demonstrates the lack of economic practicability of patent activity in a situation, when only 6–12% of patents for inventions can be supported. There are recommendations offered on how to utilize intellectual property in a scientific organization. There are methodic approaches described for making informed decisions about legal protection of research and development outcomes. Using «photonics» sub-industry as a reference, there was a publication and patent analysis presented for developing research areas in Russia and in the world. It is graphically shown, that competitive scientific-technological capacities, which are recently created and which allow Russia to remain as one of the world scientific leaders in the area, are not supported by patenting activity, and this can ultimately force Russia out from the group of key new technological markets, which we see are being formed today.